Improvised Multi-Factor Authentication for End-User Security in Cyber Physical System - Maranco, M.; Logeshwari, R.; Sivakumar, M.; Manikandan, V. (International Journal of Intelligent Systems and Applications in Engineering, 2024)
End-user security is the most important thing in day-to-day life. We use a security system for household appliances, vehicles, smartphones, etc., to protect and safeguard our things and the environment. The Cyber Physical System (CPS) contains an internet-enabled digital component. CPS security is applied in many areas, such as transport, healthcare, and all industry 4.0 applications. Multi-Factor Authentication (MFA) is one of the traditional authentications that helps enhance the security level in CPS. The typical authentication method contains a strong password, biometrics, etc. Even though the current end-user security system has implemented a legacy digital control mechanism, the system has a higher chance of getting compromised through malicious activities. The major point of the MFA approach is that intruders can be blocked at any level of the authentication scheme. This study aims at developing a secure and efficient authentication gateway. The proposed system presents enhancements to end-user security using MFA techniques. Three distinct works in this study use MFA technique. The MFA technique consists of three distinct layers. The end-user’s geo-location is considered the first security gateway by the user distance within the range of CPS and validates the user’s current position with predefined geo-location logic. One Time Password (OTP) send through e-mail is used for the second layer. Hash algorithms such as SHA256 or SALTING use the third layer implementation. The typical CPS needs to authorize and authenticate the user’s identity to ensure end-users identification in the modern security system. Efficient and secure multi-factor authentication techniques designed and evaluated on end-user digital health applications and obtained the results with the accuracy of 95.50%, 97.50% and 96.40% respect to three distinct layer authentications. The developed system also analyzed the formal and informal verifications against to the various attacks.